Seed Priming and Fortification - KALYANI SRINIVASAN; S.K. JAIN; SANJEEV SAXENA; J. RADHAMANI; MANJU UPRETY (Seed Research, 2026)
Seed priming is an essential pre-requisite for rapid, uniform germination of seeds and optimum plant stand in the field. The seed quality enhancement through seed priming has led to improvements in growers ability to achieve better plant stand both in the field and greenhouse. During seed priming, the water content of the seed increases up to 35-40 per cent of its weight, enough to activate the biochemical events, advancing seed germination processes without radicle emergence. The product of these changes persist following desiccation and are available on re-imbibition of water, during seed planting, enabling completion of seed germination rapidly, led to an uniform crop stand and synchronized flowering/fruiting. Additionally, this physiological treatment induces tolerance to certain environmental stresses (Like high temperature, low soil moisture etc), and provide invigoration treatment to partially aged seed lots. Under invigoration, metabolic repair processes in deteriorated seeds occur before onset of seed germination process. Priming can be achieved in several ways namely, imbibition in an osmotic solution [Poly ethylene glycol (PEG) or manitol] that control the water uptake (Osmo-conditioning), slow addition of water to bring the seeds to a specific water content (Hydro-priming) or mixing the seeds with a solid matrix materials like, vermiculite or diatomaceous earth and water (Solid matrix priming). If the priming solution is fortified with growth promoting substances or beneficial micro-organisms, which accelerate the germination or control the disease proliferation termed as bio-priming. The key processes involved in seed priming are, the early onset of RNA, protein synthesis and polyribosome formation. The activity of many enzymes involved in mobilization of storage reserve is triggered or de novo synthesis of important enzymes involved in pre-germination events occurs. On-farm priming is performed by soaking the seeds in water overnight, surface dried and planting the seeds on the same very day. If sowing is delayed, the seeds can be re-dried and stored, and planted as and when required. Significant yield improvements had been reported by various workers for a number of crops. The present paper discusses various methods of seed priming, its advantages, the physiological and biochemical changes involved and precautions to be observed.